Transfection microarray of nonadherent cells on an oleyl poly(ethylene glycol) ether-modified glass slide. (September 2004) - Kato, Koichi; Umezawa, Kohei; Miyake, Masato; Miyake, Jun; Nagamune, Teruyuki
Cell-based microarrays are emerging as a tool for analyzing the functions of genes in cells. However, partly due to the difficulty of cell immobilization, the application of this method has been limited to adherent cells. We previously reported a method that rapidly and strongly attached living nonadherent cells to glass slides modified with a cell membrane anchoring reagent, designated a biocompatible anchor for membrane (BAM). Here we demonstrate that plasmid DNA deposited in a defined area on BAM-modified glass slides was transfected into nonadherent K562 cells immobilized on the DNA-deposited and BAM-modified slides. This method allowed the transfection of K562 cells not only with plasmid cDNA expression vectors but also with small interfering RNA (siRNA) at a defined location on the BAM-modified slides. We expect this methodology to greatly expand the scope of current cell microarray technology.